Contributions of Experimental Psychiatry to Research on the Psychosis Prodrome - Bodatsch, Mitja; Klosterkötter, Joachim; Daumann, Jörg (Frontiers in Psychiatry, 2013)
In the recent decades, a paradigmatic change in psychosis research and treatment shifted attention towards the early and particularly the prodromal stages of illness. Despite substantial progress with regard to the neuronal underpinnings of psychosis development, the crucial biological mechanisms leading to manifest illness are yet insufficiently understood. Until today, one significant approach to elucidate the neurobiology of psychosis has been the modeling of psychotic symptoms by psychedelic substances in healthy individuals. These models bear the opportunity to evoke particular neuronal aberrations and the respective psychotic symptoms in a controlled experimental setting. In the present paper, we hypothesize that experimental psychiatry bears unique opportunities in elucidating the biological mechanisms of the prodromal stages of psychosis. Psychosis risk symptoms are attenuated, transient, and often only retrospectively reported. The respective neuronal aberrations are thought being dynamic. The correlation of unstable psychopathology with observed, e. g., neurophysiological disturbances is thus yet largely unclear. In modeling psychosis, the experimental setting allows not only for evoking particular symptoms, but for the concomitant assessment of psychopathology, neurophysiology, and neuropsychology. Herein, the glutamatergic model will be highlighted exemplarily, with special emphasis on its potential contribution to the elucidation of psychosis development. This model of psychosis appears as candidate for modeling the prodrome since it induces psychopathological, neurocognitive and neurofunctional changes that are comparable to clinical features of the prodrome. As exemplarily illustrated by the PCP/NMDA model of psychosis many aspects advocate that prodromal stages might be validly mimicked by psychedelic substances. In summary, experimental psychiatry bears the potential to further elucidate the biological mechanisms of the psychosis prodrome.